Systematic review of medical student willingness to volunteer and preparedness for pandemics and disasters. Issue 10 (7th October 2021) - Byrne, Matthew Henry Vincent; Ashcroft, James; Alexander, Laith; Wan, Jonathan C M; Harvey, Anna
Abstract : Objective: This systematic review aimed to estimate the willingness of students to volunteer during a disaster, and how well-prepared medical students are for volunteering by assessing their knowledge and medical school curriculum of disaster and pandemic medicine. Results: A total of 37 studies met inclusion criteria including 11 168 medical students and 91 medical schools. 24 studies evaluated knowledge (64.9%), 16 evaluated volunteering (43.2%) and 5 evaluated medical school curricula (13.5%). Weighted mean willingness to volunteer during a disaster was 68.4% (SD=21.7%, range=26.7%–87.8%, n=2911), and there was a significant difference between those planning to volunteer and those who actually volunteered (p<0.0001). We identified a number of modifiable barriers which may contribute to this heterogeneity. Overall, knowledge of disasters was poor with a weighted mean of 48.9% (SD=15.1%, range=37.1%–87.0%, n=2985). 36.8% of 76 medical schools curricula included teaching on disasters. However, students only received minimal teaching (2–6 hours). Conclusions: This study demonstrates that there is a large number of students who are willing to volunteer during pandemics. However, they are unlikely to be prepared for these roles as overall knowledge is poor, and this is likely due to minimal teaching on disasters at medical school. During the current COVID-19 pandemic and in future disasters, medical students may be required to volunteer as auxiliary staff. There is a need to develop infrastructure to facilitate this process as well as providing education and training to ensure students are adequately prepared to perform these roles safely.